Meta-evaluation of published studies on evaluation of health disaster preparedness exercises through a systematic review - Hojjat Sheikhbardsiri; Mohammad H Yarmohammadian; Hamid Reza Khankeh; Mahmoud Nekoei-Moghadam; Ahmad Reza Raeisi (Wolters Kluwer Medknow Publications, 2018)
Objective: Exercise evaluation is one of the most important steps and sometimes neglected in designing and taking exercises, in this stage of exercise, it systematically identifying, gathering, and interpreting related information to indicate how an exercise has fulfilled its objectives. The present study aimed to assess the most important evaluation techniques applied in evaluating health exercises for emergencies and disasters. Methods: This was meta-evaluation study through a systematic review. In this research, we searched papers based on specific and relevant keywords in research databases including ISI web of science, PubMed, Scopus, Science Direct, Ovid, ProQuest, Wiley, Google Scholar, and Persian database such as ISC and SID. The search keywords and strategies are followed; "simulation," "practice," "drill," "exercise," "instrument," "tool," "questionnaire," " measurement," "checklist," "scale," "test," "inventory," "battery," "evaluation," "assessment," "appraisal," "emergency," "disaster," "cricise," "hazard," "catastrophe,: "hospital", "prehospital," "health centers," "treatment centers," were used in combination with Boolean operators OR and AND. Results: The research findings indicate that there are different techniques and methods for data collection to evaluate performance exercises of health centers and affiliated organizations in disasters and emergencies including debriefing inventories, self-report, questionnaire, interview, observation, shooting video, and photographing, electronic equipment which can be individually or collectively used depending on exercise objectives or purposes. Conclusion: Taking exercise in the health sector is one of the important steps in preparation and implementation of disaster risk management programs. This study can be thus utilized to improve preparedness of different sectors of health system according to the latest available evaluation techniques and methods for better implementation of disaster exercise evaluation stages.